Degree of satisfaction among postlingual cochlear implant users in Oman - Al-Shasai, Nayif Ali; Ismail, Noraidah; Lamri, Marina L. Alisaputri @ Marina (Acta Scientific International Open Library, 2021)
Background and Objectives: The reliability of cochlear implant in aural rehabilitation has been reported in numerous medical and healthcare related journals and its implementation are widely seen in many rehabilitation centers. However, the use of cochlear implants can be affected by the satisfaction of cochlear implant users. In addition, there is little or no data on the satisfaction of cochlear implant user in Oman in the literature. Hence this research considers conducting the study to find out the post-cochlear implantation satisfaction of postlingual Omani adult and adolescent users.